The Reflection of July 15 on the Turkish Sports World: An Applied Research - Yücel, Ali Serdar; Talas, Mustafa; Korkmaz, Murat (My University, 2021)
The purpose of this study is to determine the perception dimension of the July 15 coup attempt in the sports world by different demographic characteristics. The research was conducted with 892 participants. a 5-point Likert scale composed of 53 questions and prepared by the researcher with the support of experts were used to obtain data for the study. All analyzes were performed with SPSS v17.0 (SPSS Science, Chicago, IL, USA). Factor analysis, Kruskal Wallis, Anova test and Independent Samples t-test were used for data analysis. It has been concluded following the study that the participants think that the July 15 coup attempt has damaged Turkish sports world, the public practices regarding Turkish sports world are largely (73%) sufficient and the perception dimensions related to the reflection of the July 15 coup attempt on the sports world differ by the variables of age, education, level of income, marital status and the working conditions of the participants.
Keywords: Sports; academic staff; institution; July 15 coup attempt